2020
DOI: 10.1007/s42974-020-00019-2
|View full text |Cite
|
Sign up to set email alerts
|

Reptile responses to vegetation structure in a grassland restored for an endangered snake

Abstract: Grassland ecosystems are among the most threatened biomes, and their restoration has become common in nature conservation. Yet restoration is rarely applied specifically for reptiles, which are among the most threatened vertebrates. The Meadow Viper (Vipera ursinii) has become extinct in most of lowland Europe, and an endangered subspecies (Vipera ursinii rakosiensis) has been a target of habitat restoration and captive breeding in Hungary since 2004. We quantified vegetation properties and the density of rept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…2007; Mizsei et al . 2020), and this appears to be the case with A. parapulchella . Further research is required to test for this possibility.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…2007; Mizsei et al . 2020), and this appears to be the case with A. parapulchella . Further research is required to test for this possibility.…”
Section: Discussionmentioning
confidence: 80%
“…Mizsei et al . (2020) detected differing responses by reptiles to vegetation characteristics in a grassland that had been restored for an endangered European snake species and concluded that management in restored grasslands should aim to increase total cover for lizards and increase structural diversity for all reptiles. The importance of tussocks in relation to reptiles has been identified in other studies (Stevens et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations